Electronic Performance Monitoring in the Digital Workplace: an Updated Systematic Literature Review (2016–2026) - Heni Sulastri; Purwanto Purwanto (Yayasan Riset dan Pengembangan Intelektual, 2026)
Electronic performance monitoring (EPM) has expanded rapidly with remote and hybrid work, enabling organizations to capture fine grained traces of employee activity through digital systems. This systematic literature review synthesizes 75 peer reviewed studies on EPM and related workplace surveillance to clarify core monitoring dimensions, employee focused outcomes, and contextual boundary conditions. Using PRISMA 2020 screening logic, we map how transparency, data granularity, and governance practices shape outcomes such as performance, well being, privacy invasion, trust, and safety compliance. The review contributes an integrative framework and highlights research gaps on longitudinal effects, equity and bias in data driven evaluation, and participatory governance for responsible monitoring.